Islamic Law Politics in The Contemporary Era (Revealing The Struggle for The Positivization of Islamic Law in Indonesia) - Muhazir, Muhazir (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This paper will discuss the politics of Islamic law until now, which still leaves debates between pros and cons parties, this debate is based on differences in views between secular Islamic groups and traditionalists, plus global political conditions increasingly influence the direction of Indonesian government legal policies. Library research is the method used in this paper, the legal policy approach and statute approach are used to analyze data found in various literature. The results of this study indicate that the struggle for the positivists of Islamic law in Indonesia is still reaping polemics, these polemics are based on three things; first, differences in understanding of the relationship between religion and state; second, the contemporary Indonesian political system is influenced by western politics; third, liberalism and communism have helped to hinder the positivists process of Islamic law in IndonesiaTulisan ini akan mendiskusikan tentang politik hukum Islam hingga saat ini yang masih menyisakan perdebatan antara pihak pro dan kontra, perdebatan ini didasari oleh perbedaan pandangan antara kelompok Islam sekuler dan Islam tradisionalis, ditambahkan lagi dengan kondisi politik global semakin mempengaruhi arah kebijakan hukum pemerintah Indonesia. Library research merupakan metode yang digunakan dalam tulisan ini, pendekatan legal policy dan statute approach digunakan untuk menganalisis data yang ditemukan dalam berbagai literatur. Hasil penelitian ini menunjukan bahwa pergulatan positivisasi hukum Islam di Indonesia masih menuai polemik, polemik tersebut didasari oleh tiga hal; pertama, perbedaan pemahaman tentang hubungan antara agama dan negara; kedua, sistem politik indonesia masa kontemporer dipengaruhi oleh politik barat; ketiga, paham liberalisme dan komunisme turut menghambat proses positivisasi hukum Islam di IndonesiaÂ Kata Kunci: Politik, Hukum Islam, Positivisasi